Corporatism, Participation and Society - Warner, Malcolm (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
After having located industrial democracy within the broader debate on corporatism, the author examines the attempts made to institutionalize developments of industrial democracy.